Recent advances in plasticity applications in metal machining: slip-line models for machining with rounded cutting edge restricted contact grooved tools. (22nd October 2007) - Wang, Xiqun; Jawahir, I.S.
This paper presents a summary of new findings on plasticity applications in metal machining, primarily covering the recent efforts on developing new slip-line models for machining with restricted contact grooved tools which involve a finite cutting edge radius. Extended application of the initially developed plane-strain, rigid-plastic slip-line fields to take account of strain, strain-rate and temperature effects is shown to provide non-unique solutions for machining with grooved tools which most commonly incorporate geometric features such as a restricted contact and a rounded cutting edge. Predictions of cutting forces, chip thickness, chip up-curl radius, temperatures and flow stresses at the primary shear zone and at the tool-chip interface, etc. are made for a range of input conditions in orthogonal machining. The practical impact of these new findings on tool-wear and cutting tool design are emphasised in this paper.